An investigation into the relationship of sea temperature and food supply to the size of the planktonic copepod Temora longicornis Müller in the North Sea. - Evans, F. (Estuarine, Coastal and Shelf Science, 1981)
In the North Sea the seasonal size pattern of Temora longicornis is irregular. Adults are always large in the spring and are then successed by smaller generations. In the summer a second peak of size may or may not occur. Autumn animals may be large or small. In this, Temora differs markedly from the previously studied Pseudocalanus sp. whose seasonal size pattern is both regular and inversely temperature-dependent. The size of Temora specimens collected monthly during the 10 years 1968–77 off Northumberland and during 1970 and 1971 at other localities in the North Sea did not closely follow the temperature curve. Rather, it is shown by correlation analysis that off Northumberland some 83% of the total size variance is explained by the abundance of the diatom Thalassiosira among those sampled, only a further 7% being explained by the introduction of sea temperature as a modifying constant. There is no evidence anywhere in the North Sea of a simple size-temperature relationship for Temora but a clear indication of a link with food availability, in particular with the diatoms Thalassiosira and Phaeoceros. Thus Temora and Pseudocalanus, planktonic copepods of similar size living side by side in the sea, produce quite different growth responses to fluctuations in temperature and food supply.